1998
DOI: 10.1007/bf01105780
|View full text |Cite
|
Sign up to set email alerts
|

Cranio-cerebral erosion: delayed diagnosis and treatment

Abstract: Cranio-cerebral erosion is a well-known complication of calvarian fracture with underlying dural tear and cerebral injury in infancy and early childhood. The anatomy, pathogenesis and natural evolution of these lesions remain obscure. The common clinical symptoms are seizures, focal neurological deficits, impairment of consciousness and a soft subgaleal mass. Three patients of cranio-cerebral erosion who underwent delayed surgery in their adult lives are presented to illustrate the common and uncommon features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Rarely, a cystoperitoneal shunt can be an option in case of non-visualisation of dural margins [4]. However, the most important step of surgery would be to achieve meticulous water-tight dural repair [2,6,33]. For this, the most commonly utilised dural substitute is pericranium because it is biocompatible, economical and has negligible risk of infection; others used being fascia lata, cadaveric or an artificial dura [2].…”
Section: Discussionmentioning
confidence: 98%
“…Rarely, a cystoperitoneal shunt can be an option in case of non-visualisation of dural margins [4]. However, the most important step of surgery would be to achieve meticulous water-tight dural repair [2,6,33]. For this, the most commonly utilised dural substitute is pericranium because it is biocompatible, economical and has negligible risk of infection; others used being fascia lata, cadaveric or an artificial dura [2].…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have demonstrated that damage to the bone, dura, and brain not only happened at the time of initial injury but also slowly worsened for months and years later. 5,19,28,38,41 During this GSF stage, neurological deficits have not usually occurred and the complications are few; therefore, it is the best period for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5,26,33,40 Pericranium, fascia lata, cadaveric dural grafts, and artificial dura have been used in this step. 16,18,21,22 In our opinion, the autologous material is the best choice because of its tissue compatibility, convenience, inexpensiveness, and rare rate of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Duraplasty is the main point (22,23). Dural tears with pulsation of CSF cause bone diastasis (4,19).…”
Section: Discussionmentioning
confidence: 99%